Comparative Chloroplast Genomics and Phylogenetic Analysis of Zygophyllum (Zygophyllaceae) of China - Zhang, Ling; Wang, Shu; Su, Chun; Harris, AJ; Zhao, Liang; Su, Na; Wang, Jun-Ru; Duan, Lei; Chang, Zhao-Yang (Frontiers in Plant Science, 2021)
The genus Zygophyllum comprises over 150 species within the plant family Zygophyllaceae. These species predominantly grow in arid and semiarid areas, and about 20 occur in northwestern China. In this study, we sampled 24 individuals of Zygophyllum representing 15 species and sequenced their complete chloroplast (cp) genomes. For comparison, we also sequenced cp genomes of two species of Peganum from China representing the closely allied family, Nitrariaceae. The 24 cp genomes of Zygophyllum were smaller and ranged in size from 104,221 to 106,286 bp, each containing a large single-copy (LSC) region (79,245–80,439 bp), a small single-copy (SSC) region (16,285–17,146 bp), and a pair of inverted repeat (IR) regions (3,792–4,466 bp). These cp genomes contained 111–112 genes each, including 74–75 protein-coding genes (PCGs), four ribosomal RNA genes, and 33 transfer RNA genes, and all cp genomes showed similar gene order, content, and structure. The cp genomes of Zygophyllum appeared to lose some genes such as ndh genes and rRNA genes, of which four rRNA genes were in the SSC region, not in the IR regions. However, the SC and IR regions had greater similarity within Zygophyllum than between the genus and Peganum. We detected nine highly variable intergenic spacers: matK-trnQ, psaC-rps15, psbZ-trnG, rps7-trnL, rps15-trnN, trnE-trnT, trnL-rpl32, trnQ-psbK, and trnS-trnG. Additionally, we identified 156 simple sequence repeat (cpSSR) markers shared among the genomes of the 24 Zygophyllum samples and seven cpSSRs that were unique to the species of Zygophyllum. These markers may be useful in future studies on genetic diversity and relationships of Zygophyllum and closely related taxa. Using the sequenced cp genomes, we reconstructed a phylogeny that strongly supported the division of Chinese Zygophyllum into herbaceous and shrubby clades. We utilized our phylogenetic results along with prior morphological studies to address several remaining taxonomic questions within Zygophyllum. Specifically, we found that Zygophyllum kaschgaricum is included within Zygophyllum xanthoxylon supporting the present treatment of the former genus Sarcozygium as a subgenus within Zygophyllum. Our results provide a foundation for future research on the genetic resources of Zygophyllum.